Novel case of resolution of hypsarrhythmia following tuber resection in a patient with infantile spasms and tuberous sclerosis - Marsh, Robert (Clin Case Rep, 2017)
This article describes a case involving the resolution of hypsarrhythmia, a generalized abnormal EEG pattern, following focal resection of a cortical tuber in a patient with tuberous sclerosis.